PEMBUATAN GAPURA TPU DESA PEKAWATAN, SEBAGAI UPAYA PEMBANGUNAN DESA SRIMINOSARI, KEC. LABUAN MARINGGAI - Ulyatun Fatonah Ulyat; Nafian Dafa Fahrezi; Anandita Vivian Salsa Bila; Fitri Damayanti; Ratna Lana Zulkarnain; Arlyan Pramana Syah Putra; Faruq Alfarez; Asta Gilang Patria; Aldrin Tridata (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2024)
The construction of a TPU gate in Pekawatan Village, Labuan Maringgai District, is a strategic effort in developing the infrastructure of Sriminosari Village. This project aims to improve the accessibility and aesthetics of the Public Cemetery (TPU) area, while strengthening the social cohesion of the community through a participatory process involving deliberation and mutual cooperation. The results of the gate construction not only provide a significant physical impact, but also strengthen residents' sense of ownership of public facilities. Apart from that, this project plays a role in increasing solidarity between residents, improving communication between social groups, and opening up economic opportunities around the TPU area. The creation of this gate has become a symbol of the success of sustainable development supported by active community participation.